FACTORS AFFECTING SAFETY BEHAVIOR AT CONSTRUCTION COMPANIES IN BATAM - Agustinus Setyawan; Lily Sudhartio; Bukti Rantau (Journal of Business Studies and Management Review, 2021)
The relatively high number of work accidents in the construction sector in Indonesia causes a lot of losses both material and non-material to workers, construction entrepreneurs and the country's image. This encourages us to investigate further what factors influence the safety behavior of workers in construction activities. This research was applied with a survey method, namely by distributing questionaires to 105 respondents. The questionnaire questions were compiled through a review of previous journals that analyzed the factors that influence worker safety behavior. The respondents sampled were Occupational Safety and Health Officer (AK3). The technique used by the researcher is purposive sampling, which is a technique to determine the sample by using a special selection method so that the sample can be properly used for processing. The authors tested the data using SPSS software with a Confirmatory Factor Analysis (CFA) approach. The results of this study lead to the conclusion that the assumptions used as a references are indeed proven to contribute to work safety behavior in construction activities. Leadership and work pressure factors both together as the dominant factors affecting worker safety behavior in construction activities in Batam are followed by the influence of co-workers, training, and company management commitment in sequence as factors contributed. Limited resources in construction activities trigger whether work safety behavior is implemented or neglected. This of course affects the performance of construction activities which leads to a commitment to completion of construction work and the objectives of the company organization in general.